Executive Board Report to the IMFC on Quota and Governance Reforms. (Policy Papers; Policy Paper, 2010)
Since the IMFC last met in April, the Executive Board has taken up the full range of quota and other governance reforms. While there has been some movement on the many complex issues, discussions have been inconclusive, and no proposal has been able to command broad support. The concluding remarks that sum up these meetings lay out the various positions taken by members of the Board (attached). The debate is continuing, and we hope to make progress on finding the possible elements of a compromise acceptable to the membership.